Heavy Mineral Distribution of Gercus Formation in Shaqlawa and Dokan Area in Northern Iraq - Alaa K. Nasif; Kareem H. Khwedim (Academic Science Journal)
From the Gercus Formation, eight samples were taken, ranging from fine grain sandstone to extremely fine grain sandstone. In comparison to other heavy metals, In the heavy metals examination, the opaque mineral had the highest percentage. Transparent minerals, such as metastable and unstable minerals, such as Amphibole, including Hornblend and Glaucophane (Epidote, staurolite, Garnet, Kyanite), reveal metamorphic sources. Mica group minerals, ultrastable minerals (Zircon, Rutile, Tourmaline) (Chiorite,Biotite and Muscovite), Mafic igneous and metamorphic rocks, as well as acidic igneous and reworked sediments, are frequently used to create heavy minerals , according to these accumulations. The ternary diagram of heavy metal stability showed that they are relatively stable because of the impact of the opaque mineral that draws the greatest attention. Both types of sandstone are used in construction.